Achieving level patient flow in an outpatient oncology clinic. Issue 1 (2nd January 2018) - Suss, Samuel; Bhuiyan, Nadia; Demirli, Kudret; Batist, Gerald
ABSTRACT: In this article, we model an oncology clinic and treatment center as a multi-stage system of interdependent stochastic processes and illustrate the mechanisms leading to excessive patient waiting times. Insights from studying the simulations of the clinic's operations point to potential improvement of the system through the planning of patient appointments to achieve level patient flow. We construct and test a novel algorithm to calculate patient appointment times so that waiting is significantly reduced. This algorithm sets patient appointments according to the series of process steps that each patient must follow and the service rates that each of these process steps can provide.